ภาพลักษณ์ตำรวจที่นำเสนอทางหนังสือพิมพ์รายวันภาษาไทย - พาฝัน สิทธิ์สงวน (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The objectives of this research are to study images of police at all position level through news presentation of the Thai daily newspapers, format and characteristics of presentation, the difference of presentation between quantitative and qualitative newspapers and to explore factors influencing the news selection. Content analysis was conducted from 360 issues of Thai Rath, Daily News, Matichon and Thaipost. 3. representatives from each newspaper were indepth-interviewed. Quantitative data were analysed by SPSS for Windows and presented through mean, percentage, t-test, and analysis of variance. Finding : 1. Majority of police image revealed through the newspapers were neutral. Between positive and negative presentation, newspaper devoted larger space to information which resulted in negative image. The significant difference was statistically tested. 2. Police story was presented the most in news reporting format. Quantitative newspaper reported about the police in gossip and commentation columns while qualitative newspaper published police news in the format of news and news in brief. 3. The qualitative newspapers devoted more space to the police story than those devoted by quantitative newspapers. The significant difference was statistically tested. 4. Seven major factors which influence the news selection for publishing were principles and policy of each newspaper, marketing competition, social and moral responsibility, public interest or taste, impact or benefit to people and society, news value, and amazing phenomena.